2017
DOI: 10.1007/s11095-017-2103-9
|View full text |Cite
|
Sign up to set email alerts
|

Complex Nature of Protein Carbonylation Specificity After Metal-Catalyzed Oxidation

Abstract: Our results show distinct patterns of protein carbonylation for HSA and G-CSF. Thus, specificity of protein carbonylation induced by metal-catalyzed oxidation is protein dependent and might be predicted by availability of transition metal binding site(s) within the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…While the role of HSP90β in cancer progression is well documented in the literature, the specific roles of filamin A and EPRS in cancer are not well studied. Our recent work on cardiac tissue and purified proteins further confirms that there is some selectivity for oxidative stress-induced carbonylation of proteins and amino acid residues within a protein [ 16 , 27 ]. We have previously demonstrated that protein functions are affected by the extent of carbonylation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…While the role of HSP90β in cancer progression is well documented in the literature, the specific roles of filamin A and EPRS in cancer are not well studied. Our recent work on cardiac tissue and purified proteins further confirms that there is some selectivity for oxidative stress-induced carbonylation of proteins and amino acid residues within a protein [ 16 , 27 ]. We have previously demonstrated that protein functions are affected by the extent of carbonylation.…”
Section: Discussionmentioning
confidence: 61%
“…Earlier studies have shown some selectivity to protein oxidation via carbonylation in cholangiocarcinoma, but mechanisms controlling this selectivity are not well understood [ 13 ]. It has been postulated that the level of protein expression, size and higher order structure of protein, number of solvent accessible amino acid residues susceptible to carbonylation, and/or distance of protein/amino acid residues from the ROS generation site may contribute to susceptibility of a specific protein for carbonylation, although more biochemical studies are needed to determine the key drivers [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrated Tc CM and NSTc CM were analyzed by liquid chromatography-tandem MS (LC/MS/MS) using Thermo Fisher Scientific Ultimate LC and Fusion Orbitrap MS. Typical settings for quantitative proteomics at FDA's Facility for Biotechnology Resources were used in the analysis (55). Proteome Discoverer 1.4 (Thermo Fisher Scientific) was used to match MS/MS spectra to peptides using the Swiss-Prot human database.…”
Section: Concentration Of CMmentioning
confidence: 99%
“…Protein concentrations were quantified, and the samples (2‐3 µg/150 µL) were reduced, alkylated, and trypsin digested as described elsewhere 27 . The resulting peptides were resolved and analyzed by nanoflow liquid chromatography coupled to tandem mass spectrometry using a Thermo Fisher Ultimate LC and Fusion Orbitrap MS by following typical settings at Food and Drug Administration’s (FDA's) Facility for Biotechnology Resources 28 . For identification, Proteome Discoverer 2.1 (Thermo Fisher Scientific) was used to match tandem mass spectometry spectra to peptides using Swiss‐Prot human database with typical setting as previously reported 29 .…”
Section: Methodsmentioning
confidence: 99%
“…27 The resulting peptides were resolved and analyzed by nanoflow liquid chromatography coupled to tandem mass spectrometry using a Thermo Fisher Ultimate LC and Fusion Orbitrap MS by following typical settings at Food and Drug Administration's (FDA's) Facility for Biotechnology Resources. 28 For identification, Proteome Discoverer 2.1 (Thermo Fisher Scientific) was used to match tandem mass spectometry spectra to peptides using Swiss-Prot human database with typical setting as previously reported. 29 For quantification using a label-free approach, the peptides were quantified by integrating (at 20 ppm tolerance) the signal intensities obtained from extracted ion chromatogram of respective peptides (Table S3).…”
Section: Nano Liquid Chromatography Tandem Mass Spectrometrymentioning
confidence: 99%